Effects of different irrigation quotas on growth characteristics and yield of seed maize in Hexi Corridor. Issue 1 (January 2021) - Xiao, Rang; He, Zhibin; Zhang, Yongling; Xiao, Zhanwen; Cheng, Hongyu; Liang, Chao
Abstract: In order to find out the optimal scheme of irrigation quota for seed corn in Zhangye, field experiments were carried out to study the effects of different irrigation quotas on the growth and yield of seed corn. Seed corn was used as test crop, drip irrigation under plastic film was used as water supply mode different irrigation quota treatment T1(4200m 3 /ha), T2(4650m 3 /ha), T3(5250m 3 /ha), T4(5400m 3 /ha), CK(5850m 3 /ha) were set up.The results showed that the plant height of T2 was the highest, reaching 154.6 cm, and the ear height of T4 was the highest, reaching 74.8cm.There was a significant difference in the double ear rate among different treatments, among which the double ear rate of T4 was the highest, reaching 19.12%, followed by T3(17.86%) and CK(15.12%), and the double ear rate of T1 was the lowest, reaching 12.98%. The empty stalk rate of T2 was the largest(7.72%), followed by T3 and T4, and the empty stalk rate of T5 was the smallest. The ear of T3 was the longest(14.74cm), and the invalid ear length of T4 was the largest(1.64cm). The grain number per ear of T4 was the largest, followed by T2, CK and T3, and CK was the smallest. Compared with T2 and T3, T4 increased by 0.23% and 4.32%(P>0.05), respectively, and significantly increased by 16.56% compared with T1.Different treatments have different responses to the yield of seed production. Among them, the T4 treatment has the largest yield, reaching 6655.8kg/hm 2, followed by T2 and T3, which are 5853.6 and 5661.9kg/hm 2, respectively.The T1 yield is the smallest, only 5362.2kg/hm 2, T4, T2 increased by 24.12% and 9.15% respectively compared with CK, significant difference. Comprehensive consideration of agronomic traits, ear economic traits, crop yield and yield increase rate and other indicators show that the optimal irrigation quota for corn planting areas in the Hexi Corridor is 5400m 3 /ha The irrigation quotas for each growth period are 825m 3 /ha at the jointing stage, 825 m 3 /ha at the big bell mouth stage, 975m 3 /ha at the tasseling stage, 975 m 3 /ha at the flowering stage, 975m 3 /ha at the filling stage, and 825 m 3 at the milking stage/ha. This research can provide theoretical and technical reference for realizing high-efficiency water-saving cultivation and industrialization development of maize seed production in the oasis irrigation area of the Hexi Corridor.